Impacts of Seasonal Nature of Employment on the Income Stability of the Farm Laborers’ Household - Paninsoro, Dhevine; Augusto, Michell Princess; Pacilan, Jelly Fe; Francis, Madelyn; Villapaña, Irish; Narvasa, Lorelyn; Cane, Rechel Mae; Ebo, Mary Jane (Journal of Interdisciplinary Perspectives, 2024)
Farm workers or laborers are essential as they provide the critical labor needed to cultivate, harvest, and sustain the agricultural processes that ensure food security and drive the agricultural economy. However, in the Philippine agriculture landscape, farm laborers are heavily affected by the seasonality of their employment. The study on the impact of seasonal employment on the income stability of the farm laborer's household remains under exploration. This participatory action research (PAR) aimed to explore the impact of the seasonal nature of employment on the income stability of the farm laborer’s household in Mapurog, Sapad, Lanao del Norte, through resource-flow activity with one-on-one interviews and observations. This is analyzed using the reflexive thematic analysis. The study revealed a complex impact of this developmental issue, including a significant reduction in income during off-peak seasons and increased reliance on informal credit sources. Children stop attending school to engage in labor and help their parents, essential daily needs remain unmet, access to healthcare is deprioritized, and mental distress pervades the community. Furthermore, the research identifies reliance on loans, credit institutions, and extended family arrangements as coping mechanisms for income instability. While these strategies demonstrate the resourcefulness and resiliency of the farm laborers, they exacerbate financial distress rather than alleviate it. The findings suggest that government policies should improve access to education, such as scholarship programs that allow children to attend school without the economic pressure to work. Additionally, financial policies could include the development of alternative and sustainable economic support systems that reduce dependence on loans and debt. Lastly, comprehensive social protection programs should be implemented to provide safety nets for vulnerable families, addressing the root causes of income instability and promoting long-term community resilience.